Analysis of the impact of health interventions on vaccination coverage for children under two years of age in municipalities of Minas Gerais - Carolina Machado Moreira; Thales Philipe Rodrigues da Silva; Mariana Coelho De Almeida Neves; Marcus Vinicius Gonçalves da Cruz; Elice Eliane Nobre Ribeiro; Silvio Ferreira Júnior; Sheila Aparecida Ferreira Lachtim; Fernanda Penido Matozinhos (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To evaluate the impact of the state action-research project on vaccination coverage in children under two years of age in the state of Minas Gerais, according to the size of the municipalities, comparing the years 2021 and 2022. Methods: This is a study nested within the state action-research project, a before-after community clinical trial carried out in 212 municipalities in the state of Minas Gerais. This study used secondary data on Vaccination Coverage (VC), Homogeneity of Vaccines (HVC) and Abandonment rate of multi-dose vaccines. After classifying municipalities by size and vaccination coverage rates were equitably classified, an analysis of secondary data on 12 immunobiologicals indicated for the age group in question and their abandonment rate of multi-dose vaccines was carried out. Results: There was an increase in the proportion of municipalities classified as small that reached the vaccination coverage target set by the National Immunization Program (PNI) after the action-research project was carried out. There was an increase in the proportion of small municipalities classified as having a low abandonment rate for the rotavirus vaccine, in the adequate homogeneity of vaccination coverage and in the classification of risk as very low risk and low and medium risk, all with a statistically significant difference. Conclusion: There was an influence of municipal size on the effectiveness of the actions applied to increase vaccination coverage, explaining that proposing individualized actions for each municipality is essential to improve vaccination coverage.